Component Identification and Functional Analysis of Outer Membrane Vesicles Released by Avibacterium paragallinarum - Mei, Chen; Sun, Ai-hua; Blackall, Patrick J.; Xian, Hong; Li, Shu-fang; Gong, Yu-mei; Wang, Hong-jun (Frontiers in Microbiology, 2020)
Avibacterium paragallinarum, the causative agent of infectious coryza, is known to release outer membrane vesicles (OMVs). The composition, bioactivities and functional properties of the OMVs of Av. paragallinarum were investigated in this study. Following extraction and purification, the OMVs were observed to be spherical in shape, with diameters ranging from 20 to 300 nm. The vesicles contained high levels of endotoxin as well as genomic DNA. The molecular weights of the OMV-contained protein fragments were mostly concentrated at 65 kD and 13 kD. The components of the OMV proteins were mainly various functional enzymes (e.g. ATP-dependent RNA helicase), structural components (e.g. streptomycin B receptor and membrane protein), and some hypothetical proteins with unknown functions. The expression levels of inflammation-related factors, such as interleukin (IL) 2 (IL-2), IL-6, IL-1β, IL-10 and inducible nitric oxide synthase (iNOs), were significantly up-regulated in HD11 chicken macrophage-like cells incubated with OMVs. Serum IgG antibodies were measured after an intramuscular injection of OMVs and an adjuvant into SPF chickens. The vaccinated chickens were then challenged by Av. paragallinarum of homologous and heterologous serovars. It was noted that the vaccinated chickens produced specific IgG antibodies against Av. paragallinarum, with a protection rate of 70% against Av. paragallinarum serovar A. However, the cross-protective effects of OMVs against heterologous challenge with serovars B and C were weaker. Overall, this study laid a foundation for further unraveling the functional roles of OMVs released by Av. paragallinarum.